Recent developments in miniemulsion polymerization - Aizpurua, I. (1996)
Some developments in miniemulsion polymerization aiming at taking advantage of its unique mechanisms minimizing the drawbacks of this technique are discussed. The discussion ineludes preparation of highly concentrated latexes, miniemulsion polymerization in continuous stirred tank reactors (CSTRs), and elimination of the low molecular weight hydrophobe.